Student Engagement Models: Parental Support, Academic Self-Efficacy, and the Teacher-Student Relationship - Khoirunnisa; Eny Purwandari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
Student engagement is the basis for academic and social success in online learning. The study aimed to examine the measurement and structural models and empirically test the relationship between parental support, academic self-efficacy, teacher-student relationship, and student engagement. The number of research samples was 323 junior high school students in Cirebon City, coming from 4 schools (public and private) which were obtained by multistage cluster random. The instrument uses a scale of student engagement, parental support, academic self-efficacy, and teacher-student relationship. Data analysis using structural equation modeling (SEM) with LISREL 8.8 program. The results showed that the overall fit test of the student engagement model was fit: Chi-square (p) = 146.71 (.00), df = 59, RMSEA = .068, SRMR =.05; CFI = .99, NNFI =.99; GFI = .93. The student engagement model is supported by parental support, academic self-efficacy, and the teacher-student relationship. The findings have contributed to strategies for increasing student engagement through parental support, teacher-student relationships, and academic self-efficacy.  Keywords: Student Engagement Model, Parental Support, Academic Self-Efficacy